Effectiveness Of Farmer Group Communication In Farming In Karanjang Hamlet, Wayame Village - Rizal Z Notanubun; RA Far Far; PM Puttileihalat (International Journal of Economics, Business and Innovation Research, 2024)
To find out the communication between farmer groups carried out by farmers in farming in Kranjang Hamlet. To find out the effectiveness of farmer group communication in managing farming in Kranjang Hamlet. To find out the effectiveness of farmer group communication in managing farming. farming in Kranjang Hamlet. This research has two types of data, namely quantitative data and qualitative data which will be processed and analyzed. The instruments used are questionnaires, in-depth interview guides and field observations. Agricultural extension seeks to change the behavior (knowledge, attitudes and skills) of farmers so that they are willing and able to apply human agricultural technology innovations to overcome the problems they face. Communication plays an important role in life Effective communication is important and is a necessity for everyone, including in the activities of members of the Kranjang Hamlet farmer group, the quality of leadership, dynamic discussions and high group cohesion indicate successful communication within the farmer group. Effective communication is important to create individual empowerment in the group. Overall, communication in all farmer groups is in the high category both in terms of understanding, enjoyment, influencing attitudes, building better relationships, and positive actions that are effective and contribute to the success of group activities in Kranjang Hamlet.